Study of conditions of gully formation in mountain regions of South-East Kazakhstan with use of GIS-technologies - Khalykov, Yerkebulan; Lyy, Yuisya; Sarybaev, Edil; Togys, Maulen; Uksukbayeva, Saule; Sharapkhanova, Zhanerke (Geodesy and Cartography, 2021)
In the article the results of field and laboratory researches of gully erosion in the mountains of Zhetysu Alatau of south-east Kazakhstan are considered. Mountain ridge Malaisary was chosen for study of gully erosion. Malaisary ridge is the western ridge of Zhetysu Alatau mountains in the south-east Kazakhstan. Foothills and plain territories of southeast Kazakhstan are characterized by favorable conditions for the development of erosion processes. There was conducted stationary monitoring (yearly in October from 2013 to 2018) of gully erosion development on the Malaisary ridge from 2013 to 2018. Most of gullies of studied ridge show development in the top part and extend in the width mainly due to fluvial processes. There were studied the natural-anthropogenic factors influencing development of gully erosion; the morphometric characteristic received using the modern devices and satellite images are provided. The determined factors of development of gullies on Malaisary ridge are mechanical substratum composition, atmospheric precipitation (spring runoff, summer rainfalls), steepness and length of the slopes. The received materials allow concluding that gully erosion is the most active factor of the ridge relief transformation. Intensive gully erosion development increases ecological tension of natural-anthropogenic environment in the region. Growth of gully net and its active development deteriorates quality of agricultural lands and create threat to road objects and residential area infrastructure in the region.